P779Constructing a new myocardial bioprosthesis for cardiac repair. (15th July 2014) - Prat-Vidal, C; Galvez-Monton, C; Perea-Gil, I; Roura, S; Llucia-Valldeperas, A; Soler-Botija, C; Bayes-Genis, A
Abstract: Purpose: Currently, progenitor cells and tissue engineering are being proposed as an addition to conventional therapies of myocardial infarction. Engineered tissue grafts and myocardial bioprostheses aim to improve cellular engraftment and viability, combining cellular components with supporting materials. Here, we proposed a new bioprosthesis composed by human pericardial-derived scaffold and adipose tissue progenitor cells (ATPCs) for human cardiac repair. Methods: Surgical samples of human pericardium were obtained from 39 patients (27 males, 12 females; mean age 68±11 years; range 50 to 84 years) undergoing cardiothoracic surgery, with apparently healthy pericardia. For decellularization, a protocol combining detergents, enzymatic digestion and agitation was used and remaining DNA was quantified by spectrophotometry. Decellularized pericardia were lyophilized by drying under vacuum, sterilized by gamma irradiation and analyzed by scanning electron microscopy. To assess in vitro degradation, lyophilized scaffolds were incubated with 0.1% collagenase I. Recellularization was carried out by mixing equal volume of cell suspension (GFP+-ATPCs in 10% sucrose) with hydrogel (RAD16-I 0.3% in 10% sucrose). In vitro biocompatibility was tested by loading hydrogel (with or without GFP+-ATPCs) in the pericardial scaffolds and then cultured 1 week under standard conditions. Masson's trichrome staining was performed to verify recellularization and cell viability was analyzed with a commercial kit. Results: After decellularization, human pericardia were pale collagen scaffolds free of cellular debris and rich in filaments. Total DNA content within the acellular scaffold was significantly lower (P=0.012) than that obtained for native pericardium (66±24 ng DNA/mg scaffold vs. 214±79 ng DNA/mg pericardium, respectively). Nuclei staining with Hoechst 33342 confirmed no residual nucleic acids in decellularized pericardium. Furthermore, biodegradability experiments showed that scaffolds lost 70% of their original weight after collagenase I treatment (P<0.001). After 1 week of recellularization, the majority of GFP+-ATPCs remained viable inside the bioprosthesis. Conclusions: Decellularization protocol efficiently removed all cellular and nuclear material of human pericardial tissue. In addition, evidences of biocompatibility and biodegradation of the resulting bioprosthesis were further provided in vitro. This pericardial-based bioprosthesis could be deliverable via currently used, minimally invasive methods, to promote cell homing into damaged myocardium.